Epizootology Of Bovicolliosis Of Goats - Boltaev D.M; Pulotov F.S (Zien Journals, 2023)
The article describes the information about the causative agent of bovicolosis, one of the most common ectoparasitic diseases among goats in recent years.
Keywords: bovicola; bovicolosis; wool eaters